An incurable case of love. Volume 7 - Enjoji, Maki (Shojo beat manga., 2021)
"Even when they're apart and lonely, they believe in their love. Our Valiant One and the Dark Lord have an incurable case of love! This is the grand finale! Nanase became a nurse to chase after Dr. Kairi Tendo. Before Kairi travels abroad to study, the two decide to do the things that lovers do! Their love deepens in their limited time together, but a problem arises concerning Kairi's succession in the family business! What will happen to Nanase and Kairi's romance?!"--page [4] of cover.